Memoria e lutto in Fragmentos de un libro futuro di José Ángel Valente - Pérez-Ugena, Julio (L’ospite ingrato, 2024)
Starting with the mournful character in the motifs, themes, and structural design of José Ángel Valente’s latest book, in this essay I also address the ways in which grief manifests itself in his language and prosody. I have thus tried to show how grief is not only related to death, it is intrinsic to writing and can be fruitful for the poem, the poet and the reader. From meditations on personal experiences to those on historical catastrophes, including spiritual ones, Valente’s poetry, aware of its own fragility, modulates itself in the multiplicity of the ‘counter-word’ linked to memory in the face of the violence of history.